High-Performance Thin-LayerChromatographic Fingerprints ofFlavonoids and Phenol Carboxylic Acids forStandardization ofIranian Species of the Genus Crataegus L.: Standardization of Iranian Crataegusspp. By HPTLC fingerprintingfingerprint - Yaghoub Amanzadeh; Mahnaz Khanavi; Mahboubeh Khatamsaz; Afsaneh Rajabi; Seyed Esmaeil Sadat Ebrahimi (Iranian Journal of Pharmaceutical Sciences, 2007)
Eight samples of flowering tops from six species of the genus CrataegusL.,commonly called Hawthorn, from different geographic locations of Iran werestandardized according to German Pharmacopoeia monograph on Crataegi foliumcum flore(hawthorn leaf with flower) by high-performance thin-layer chromatograph-ic (HPTLC) fingerprinting combining with digital scanning profiling of their majorpolyphenolics as flavonoids and phenol carboxylic acids (PCAs). All of the species,except one, contained rutin and hyperoside as flavonoids, and chlorogenic andcaffeic acid as PCAs in their flowering tops samples. HPTLC fingerprinting, ratherthan conventional TLC in the DAB 1997 hawthorn monograph, gave faster and moreefficient qualitative and quantitative analysis of hawthorn plant material and theirextracts that was appropriate for standardization of Crataegus spp. The correspondingdigital scanning profiling provided an easy way for quantitative comparisons amongthe species. The HPTLC fingerprint is also suitable for rapid and simple authenticationand comparison of subtle differences among samples of identical plant resource, butfrom different geographic locations.